(untitled) - Spencer, David (Pyrmont, NSW, 2014)
This is the first book in the Australian market to bring together the growing number of ADR cases and articles into one text. The text presents an objective cross-section of the various views on the topics surrounding dispute resolution and gives readers a guide to the practical application of the law.
Keywords: Dispute resolution (Law),Giải quyết tranh chấp (Luật); Australia,Úc